Optimizing PVA/Chitosan Films with Acid-Functionalized MWCNTs: A Multifaceted Study on Performance Enhancement - Karatas, Mukaddes; Erzen, Buket; Deniz, Sermin; Aydogmus, Ercan; Orhan, Ramazan (Mdpi, 2026)
Poly(vinyl alcohol)/chitosan (PVA/CS) biodegradable films reinforced with acid-functionalized multi-walled carbon nanotubes (f-MWCNTs) were fabricated via solution casting to investigate the effects of nanotube incorporation on structural, mechanical, thermal, dielectric, and physicochemical properties. Unlike conventional CNT-reinforced systems, this study focuses on the role of acid functionalization in improving nanotube dispersion and interfacial interactions, enabling simultaneous enhancement of multiple performance characteristics. Fourier transform infrared spectroscopy (FTIR) analysis confirmed strong intermolecular interactions between PVA/CS functional groups and carboxyl groups on f-MWCNTs, while scanning electron microscopy (SEM) revealed homogeneous nanotube dispersion at low loadings and partial aggregation at higher contents. X-ray diffraction (XRD) indicated that crystallinity was modified in a non-monotonic manner with increasing nanotube concentration due to competing nucleation and chain-restriction effects, while dielectric measurements showed an increase in dielectric constant from 3.78 to 4.27 as a result of enhanced interfacial polarization. The thermal conductivity improved from 0.195 to 0.247 W & centerdot;m-1 & centerdot;K-1, and tensile strength increased from 19.8 to 24.5 MPa at 0.2 wt.% f-MWCNT, with elongation at break decreasing from 37.9% to 25.1%, reflecting increased stiffness. The degree of swelling and water solubility decreased with higher nanotube content, indicating reduced hydrophilicity and enhanced structural compactness. The results provide new insights into how surface-functionalized nanofillers can be used to tailor the multifunctional performance of biodegradable polymer nanocomposite films, highlighting their potential in advanced applications such as sustainable packaging, flexible electronics, sensors, and membrane technologies.
Keywords: PVA/chitosan films; acid-functionalized MWCNT; nanocomposite films; mechanical properties; swelling behavior